The Effectiveness of Using Warm-Up Activvities in Language Teaching - Khakimova Dilshoda Oybek qizi (International Journal on Integrated Education, 2023)
This article examines the meaning, types and the role of warm-up activities in language learning process, and methods of introducing them into classroom are also mentioned in the paper.